2011
DOI: 10.1186/1478-7547-9-17
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the cost-effectiveness of lifestyle intervention programmes to prevent diabetes based on an example from Germany: Markov modelling

Abstract: BackgroundType 2 diabetes mellitus (T2D) poses a large worldwide burden for health care systems. One possible tool to decrease this burden is primary prevention. As it is unethical to wait until perfect data are available to conclude whether T2D primary prevention intervention programmes are cost-effective, we need a model that simulates the effect of prevention initiatives. Thus, the aim of this study is to investigate the long-term cost-effectiveness of lifestyle intervention programmes for the prevention of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 25 publications
0
51
0
4
Order By: Relevance
“…tarafından diyabet hastalığı ile ilgili tanımlanmış dört farklı durum ve markov geçiş olasılıkları ile maliyet ve fayda (utility) değerleri kullanılarak simülasyon uygulaması yapılmıştır. 11 …”
Section: Songül çInaroğluunclassified
See 2 more Smart Citations
“…tarafından diyabet hastalığı ile ilgili tanımlanmış dört farklı durum ve markov geçiş olasılıkları ile maliyet ve fayda (utility) değerleri kullanılarak simülasyon uygulaması yapılmıştır. 11 …”
Section: Songül çInaroğluunclassified
“…tarafından diyabet konusunda yapılan çalışmada kullanılan durumlar arası geçiş olasılıkları, maliyet ve değerler kullanılmıştır. 11 Yaşam tarzı ile ilgili müdahalelerin MD bakımından incelendiği bu modelde, döngü süresi bir yıl olarak belirlenmiştir. Çalışmada modelin başlangıcında bireylerin %16'sı BGT iken, %84'ü NGT ve sıfır kişi T2D'dir.…”
Section: Veri̇leri̇n Anali̇zi̇unclassified
See 1 more Smart Citation
“…Short time-horizon studies have shown prediabetes lifestyle interventions to be cost-effective and even cost saving. Long time-horizon studies based on 10 to 30 year predictive mathematical models have used different models with different data, and have come to different conclusions about the cost-effectiveness of prediabetes lifestyle interventions [54][55][56][68][69][70][71][72][73][74][75][76][77]. Predictive models are useful, but they also have limitations.…”
Section: Cost-effectiveness Of Diabetes Preventionmentioning
confidence: 99%
“…The cost-effectiveness of lifestyle interventions has been examined in a number of clinical trials and computer modelling simulations. Although pharmacological interventions have also been shown to prevent diabetes, the cost effectiveness and risk-benefit ratio are less clear [32][33][34][53][54][55][56][57][58][59][60][61][62][63].…”
Section: Cost-effectiveness Of Diabetes Preventionmentioning
confidence: 99%